Wanita Karir Perspektif Mubadalah Ky Fakih Dan Kedudukannya Dalam Hukum Islam - Wahyu Nur Alfiyan (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
Abstract: Career women generally experience difficulties in balancing their role in the household and their role in the career. If this condition occurs for a long time, it will lead to family and work conflicts which will eventually result in disharmony in the household. Career women have roles and burdens that are not light, both as career women with all their responsibilities, and as wives who must obey and obey their husbands and carry out their obligations as wives, as well as mothers for their sons and daughters who need balanced thoughts and attention. From the problems above, the researcher took the formulation of the problem as follows: 1). How are Career Women according to the Concept of Mub is Ky Fakih and 2). What is the Position of Career Women in Islam. This study uses a qualitative research method with literature review in which researchers analyze career women using two concepts, namely Mubadallah and Islam. From the results of this analysis, it explains that career women according to the concept of mubadallah Ky Fakih, namely that women are allowed to become career women because in Islam Allah SWT created humans with male and female sexes, they are not differentiated in terms of worship, only their biological factors are differentiate. Meanwhile, career women, according to Islam, women have the freedom to work, do not leave their responsibilities and are the mothers of their children and can maintain their nature as well as their religion.